(3fgGjI GdeWdH aj OQGjI GdePgHs - (3YHO Gdedc Hf YHO Gddg Hf jhSa Hf eMeO GdoLnhrjfj, CHh GdeYGdj, Qcf GdOjf, GdedbH HEeGe GdMQejf , J (B487 (3g`s
(3ChdgG (B:s
(3HGH GdZSd ddLeYI s
(3BNQgG (B:s
(3HGH GdHjY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B11 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1990s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(1130) s
Keywords: (3Gdabg GdTGaYjs